Daughters of the veil [videorecording] impact of education on women in Pakistan - Griffiths, Steven; Gill, Ian; Salamon, Robert (Asian Development Bank, 1997)
In Pakistan 3 out of 4 women cannot read or write. In a highly traditional and mainly rural society, women are confined to the home or the field. Education can break the cycle of seclusion and ignorance. This video shows how education is helping four young women develop their potential.